Organoleptic Test Analysis of Pukis With Red Bean Flour and Mocaf Flour Substitution with the Addition of Bananas - Syafira Nurul Azmi; Puteri Dwi Andita (Program Studi Teknologi Pangan Fakultas Pertanian UNSOED, 2026)
Background: As modern food develops, traditional food is increasingly being abandoned, so it is necessary to modify traditional food to produce food innovations that are able to compete in the modern food market. There are several alternative modifications of traditional cakes such as pukis cakes that are modified in their raw materials, one of which is pukis cakes with substitution of red bean flour and mocaf flour, namely flour with a low glycemic index with the addition of bananas as a sugar substitute. Purpose: This study aims to analyze the organoleptic test of making pukis with substitution of red bean flour and mocaf flour with the addition of bananas to find out the best formula. Method: This study used a Completely Randomized Design (CRD) with 3 treatment levels. The formulation used was a combination of red bean flour and mocaf flour, namely 100: 0 (F1), 50: 50 (F2), and 75: 25 (F3). Result: The results of the study showed that the substitution of red bean flour and mocaf flour with the addition of bananas to the sensory aspects of pukis did not have a significant effect on aroma, taste, color, texture, and aftertaste. The best formula was P2 with a composition of 50% red bean flour and 50% mocaf flour, which was overall preferred by the panelists.